Mothers’ experiences implementing Local Food-Based Feeding Recommendations (LFFRs) for stunted children in Malang, Indonesia: a narrative study - Hayu Iyaka Nastaina; Nia Novita Wirawan; Annisa Rizky Maulidiana (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2025)
Local Food-Based Feeding Recommendations (LFFRs) were developed to fulfill the nutritional needs of stunted toddlers but remain underexplored in community settings. This study systematically examined child feeding practices based on LFFRs and investigated the contextual factors, challenges, and strategic efforts influencing their implementation by mothers of toddlers. A qualitative narrative design was used. Six mothers of toddlers were purposively selected and participated in in-depth interviews, each lasting 45–60 min. Data collection was conducted over two months. Thematic analysis was used to identify key patterns, and source triangulation was applied to enhance the credibility and trustworthiness of the findings. The analysis of the interview data revealed five main categories and 12 subthemes. These main categories were: (1) Overview of LFFRs implementation, (2) Factors influencing TIPs LFFRs, (3) Challenges in implementing TIPs LFFRs, and (4) Strategies to improve children's intake. The findings revealed varied consumption patterns, with animal-based proteins (mainly eggs and chicken) dominating, limited intake of plant-based proteins (primarily tofu and tempeh), and fluctuating fruit, vegetable, and dairy consumption. Key barriers included children’s food preferences, time constraints, limited knowledge of local food preparation (e.g., wader fish and fresh milk), and perceived food-related risks. Adaptive strategies, such as diverse food processing and small frequent feedings, were employed by some mothers. These findings highlight the need for context-specific nutrition education and practical support for mothers, complemented by further research, evidence-based visual modules, practical caregiver training, and strengthened cross-sectoral collaboration to ensure the sustainable implementation of LFFRs and local food availability.